Preserving Appearances: Mussolini, International Politics and the Search for a Negotiated Settlement during the Ethiopian War (Il Risorgimento. Rivista di storia moderna e contemporanea, 2025)
The debate on whether the Italo-Ethiopian War could have been avoided or resolved through a negotiated settlement has divided scholars over the years. Some argue that Mussolini was determined to fully conquer the Negus’ empire, while others believe he preferred an agreement with Great Britain and France from the outset of the dispute. However, the interplay between diplomatic documents and the memoirs of key figures helps to outline a precise picture. This analysis builds on established historiographical paradigms to explore the coherence between Fascist foreign policy, the great powers’ desire to maintain international balance, and the dictator’s behavior during the crisis, ultimately highlighting the shared need of all actors to preserve appearances.
Keywords: Italo-Ethiopian War, Fascist foreign policy, Mussolini, British imperial policy, French security policy, International politics in the interwar period